2022
DOI: 10.3390/ma15020638
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Anisotropic Dynamic Elastic Constants of Additive Manufactured and Wrought Ti6Al4V Alloys

Abstract: Additively manufactured (AM) materials and hot rolled materials are typically orthotropic, and exhibit anisotropic elastic properties. This paper elucidates the anisotropic elastic properties (Young’s modulus, shear modulus, and Poisson’s ratio) of Ti6Al4V alloy in four different conditions: three AM (by selective laser melting, SLM, electron beam melting, EBM, and directed energy deposition, DED, processes) and one wrought alloy (for comparison). A specially designed polygon sample allowed measurement of 12 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…[ 7 ] This gap in understanding was highlighted in a study by Tevet et al, which explored the anisotropy of Ti6Al4V parts fabricated by AM in comparison to conventional methods. [ 113 ] Interestingly, the study revealed only minimal differences in elastic characteristics across various orientations. It is crucial for designers to consider the variation in elastic characteristics resulting from different manufacturing techniques and directions (i.e., AM build direction), because it can significantly affect the vibration response of the built parts.…”
Section: Future Directions and Challengesmentioning
confidence: 83%
“…[ 7 ] This gap in understanding was highlighted in a study by Tevet et al, which explored the anisotropy of Ti6Al4V parts fabricated by AM in comparison to conventional methods. [ 113 ] Interestingly, the study revealed only minimal differences in elastic characteristics across various orientations. It is crucial for designers to consider the variation in elastic characteristics resulting from different manufacturing techniques and directions (i.e., AM build direction), because it can significantly affect the vibration response of the built parts.…”
Section: Future Directions and Challengesmentioning
confidence: 83%
“…Materials used in 3D-printing mainly include titanium alloy, porous tantalum metal, and polyether ether ketone[ 21 - 23 ]. In our study, we used the titanium alloy, Ti 6 Al 4 V, as it offers many useful advantages.…”
Section: Discussionmentioning
confidence: 99%
“…When the anisotropic behavior is considered, more information on ultrasonic wave velocities in different directions is required to derive more components in the elastic stiffness matrix. For instance, Tevet et al fabricated specially designed polygon samples to allow measurement of 12 sound wave velocities to determine the anisotropic dynamic elastic constants of AM Ti6Al4V Alloys [21]. A multiple mode ultrasonic transducer and measurement system should be developed to avoid changing the coupling condition and obtain more information on wave velocities.…”
Section: Introductionmentioning
confidence: 99%